The Economic Lives of Young Women in the Time of Ebola : Lessons from an Empowerment Program - Bandiera, Oriana; Buehren, Niklas; Goldstein, Markus; Rasul, Imran; Smurra, Andrea (World Bank, Washington, DC, 2019)
This paper evaluates an intervention to raise young women's economic empowerment in Sierra Leone, where women frequently experience sexual violence and face multiple economic disadvantages. The intervention provides them with a protective space (a club) where they can find support, receive information on health and reproductive issues, and vocational training. Unexpectedly, the post-baseline period coincided with the 2014 Ebola outbreak. The analysis leverages quasi-random across-village variation in the severity of Ebola-related disruption, and random assignment of villages to the intervention to document the impact of the Ebola outbreak on the economic lives of 4,700 women tracked over the crisis, and any ameliorating role played by the intervention. In highly disrupted control villages, the crisis leads younger girls to spend significantly more time with men, out-of-wedlock pregnancies rise, and as a result, they experience a persistent 16 percentage points drop in school enrolment post-crisis. These adverse effects are almost entirely reversed in treated villages because the intervention enables young girls to allocate time away from men, preventing out-of-wedlock pregnancies and enabling them to re-enrol in school post-crisis. In treated villages, the unavailability of young women leads some older girls to use transactional sex as a coping strategy. The intervention causes them to increase contraceptive use so this does not translate into higher fertility. The analysis pinpoints the mechanisms through which the severity of the aggregate shock impacts the economic lives of young women and shows how interventions in times of crisis can interlink outcomes across younger and older cohorts.